Difficulties associated with outpatient management of drug abusers by general practitioners. A cross-sectional survey of general practitioners with and without methadone patients in Switzerland - Pécoud Alain; Besson Jacques; Pelet Anne; Favrat Bernard (BMC Family Practice, 2005)
Abstract Background In Switzerland, general practitioners (GPs) manage most of the patients receiving methadone maintenance treatment (MMT). Methods Using a cross-sectional postal survey of GPs who treat MMT patients and GPs who do not, we studied the difficulties encountered in the out-patient management of drug-addicted patients. We sent a questionnaire to every GP with MMT patients (556) in the French-speaking part of Switzerland (1,757,000 inhabitants). We sent another shorter questionnaire to primary care physicians without MMT patients living in the Swiss Canton of Vaud. Results The response rate was 63.3%. The highest methadone dose given by GPs to MMT patients averaged 120.4 mg/day. When asked about help they would like to be given, GPs with MMT patients primarily mentioned the importance of receiving adequate fees for the care they provide. Secondly, they mentioned the importance of better training, better knowledge of psychiatric pathologies, and discussion groups on practical cases. GPs without MMT patients refuse to treat these patients mostly for emotional and relational reasons. Conclusion GPs encounter financial, relational and emotional difficulties with MMT patients. They desire better fees for services and better training.